Microwave-Assisted Catalyst-Free Hydride Transfer: Synthesis and Evaluation of Antioxidant Properties of N-Benzylindolines - Boruah, Aditi; Deb, Mohit L.; Baruah, Pranjal K. (Synlett, 2024)
We report a catalyst-free intermolecular hydride-transfer reaction to synthesize N-benzylindolines under microwave heating in the absence of a solvent. The reactions are performed by taking indoline (two equivalents) with aryl aldehydes, which give good yields of products. Tetrahydroisoquinoline can also be used in place of indoline to give excellent yields of the expected products. A mechanism has also been proposed. The antioxidant properties of all the N-benzylindolines were tested and compared with that of ascorbic acid, showing that some of them are powerful antioxidants.
Keywords: microwave heating; hydride transfer; catalyst-free reaction; antioxidants; benzylindolines